A Comparative Study of the Effect of Different Signals of the Power System Stabilizer on the Stability of Electric Power Systems - Mohammed Abd El-hamid; Alaa Aldin housam Aldin; Emad komaira (Tishreen University, 2019)
يهدف هذا البحث إلى تحسين استقرار نظم الطاقة الكهربائية باستخدام مخمد اهتزاز تقليدي يقدم تخامد إضافي عن طريق تقديم إشارة جهد على دخل نظام التهييج من أجل توليد عزم تخامد متوافق بالطور مع السرعة. لقد تم في البحث تطبيق إشارات دخل مختلفة لمخمد الاهتزاز تمثّل تغيّر التردد، تغيّر الاستطاعة المسرعة وتغيّر السرعة. رسمت الاستجابات الزمنية لتغيّر كلٍ من السرعة والجهد الطرفي  وزاوية القدرة بدلالة الزمن عند حدوث اضطراب في تغيّر الاستطاعة الميكانيكية، كما تم مقارنة أداء النظام بوجود وجود مخمد الاهتزاز وبدونه. أظهرت النتائج أن استخدام مخمد اهتزاز بتغذية عكسية من إشارة تغير السرعة يعطي أفضل تخامد للنظام وذلك لأن مخمد الاهتزاز يعطي تخامد متوافق بالطور مع السرعة The objective of this research is to improve the electrical power system stability using the conventional power system stabilizer that gives additional damping by providing voltage signal to the excitation system input to generate damping torque that is in phase with the speed. It has applied different signals to the power system stabilizer, speed change, accelerator power change, and frequency change.  The time responses of rotor angle change, speed change, terminal voltage change   have been drawn when a disturbance in mechanical power happened. Moreover, the system performance of the system has been compared with and without power system stabilizer. Results showed that using power system stabilizer with a feedback signal from speed change gives the best damping for the system. This is because the power system stabilizer gives damping torque in phase with the speed.